THE RELATIONSHIP BETWEEN (IN) EFFICIENCY AND STABILITY IN THE PUBLIC SERVICE: THE RELATIONSHIP BETWEEN (IN) EFFICIENCY AND STABILITY IN THE PUBLIC SERVICE - Oliveira, Elizangela de; Cruz , Ênio Valdir Pereira da; Oliveira , Diego Allan de Abreu; Ruwer, Léia Maria Erlich; Pedrosa, Rafael Alves; Andrade, Darly Fernando; Redin, Ezequiel (Brazilian Journal of Production Engineering, 2020)
The present study addresses the lack or lack of efficiency in the performance of the public service, and the relationship of this problem with the prerogative of stability in that function. The objective was to research studies already carried out in the Applied Social Sciences, in the period 2000-2020, about the stability and efficiency / inefficiency of the public servant and compose an outline of the researches that bring in their notes elements that relate these aspects. To this end, an exploratory study of a bibliographic nature was carried out, which included content analysis in a sample of 20 selected articles, from public online databases. The results of the study do not confirm the existing causal relationship, but point to the existence of tools that, when properly implemented, may change this reality of inefficiency in the public service.
Keywords: Public Service; Inefficiency; Stability